2019
DOI: 10.3390/nano9121723
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing Mechanism of Reduced Graphene Oxide on Flexural Strength of Geopolymers: A Synergetic Analysis of Hydration and Chemical Composition

Abstract: With the development of nanotechnology, reduced graphene oxide (rGO) has been used to improve the flexural strength of geopolymers. However, the reinforcing mechanism of rGO nanosheets on the flexural strength of geopolymers remains unclear. Here, this reinforcing mechanism was investigated from the perspectives of hydration and chemical composition. The effect of the reduction degree on rGO-reinforced geopolymers was also studied using isothermal calorimetry (IC), X-ray diffraction (XRD), and nuclear magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Long et al [ 69 ] conducted a study on the reinforcing mechanism of reduced graphene oxide (rGO) nanosheets on GBFS-based geopolymer mortars. The addition of rGO nanosheets remarkably increased the flexural strength properties of the samples.…”
Section: Geopolymer Cements: Basic Features and Novel Advancesmentioning
confidence: 99%
“…Long et al [ 69 ] conducted a study on the reinforcing mechanism of reduced graphene oxide (rGO) nanosheets on GBFS-based geopolymer mortars. The addition of rGO nanosheets remarkably increased the flexural strength properties of the samples.…”
Section: Geopolymer Cements: Basic Features and Novel Advancesmentioning
confidence: 99%
“…This result was due to the increase of low-density waste EPS (28 kg/m 3 ). Note that the addition of rGO slightly accelerated the alkali reaction, which leads to more reaction products and increases the density of rGO-WEA [46,48]. However, the rGO content adopted in this study was relatively low (0.04 wt.%).…”
Section: Densitymentioning
confidence: 86%
“…Particularly, reduced graphene oxide (rGO) is used in construction for its large specific surface area, favorable mechanical strength, and high toughness [44][45][46][47]. In addition to this superior performance, rGO can effectively disperse in the highly alkaline environment of AAMs matrix (pH~12.5) due to electrostatic stabilization and significantly improve its mechanical properties [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…It is vital to retain a small amount of water in the cured geopolymer to avoid dehydration and excessive shrinkage due to long curing times at high temperatures (Van Jaarsveld et al, 2002). It was found that the flexural strength increases to about 29% for slag geopolymer composite filled with rGO steamed cured for 48 h at 60°C (Long et al, 2019a). There are three reasons for the geopolymer strength improvement.…”
Section: Flexural Analysis On the Graphene Reinforced Geopolymer Nanocompositesmentioning
confidence: 99%
“…At the same time, The residual oxygen functional group helps in dispersing rGO in alkaline solution. However, when stirring temperature is further increased to 80°C, the flexural strength is observed to decline due to severe structural defects of RGO (Long et al, 2019a). Extreme stirring heat in alkaline solution not only causes reduction of graphene to GO, but also exhibits wrinkles on GO structure (Deng and Berry, 2016).…”
Section: Flexural Analysis On the Graphene Reinforced Geopolymer Nanocompositesmentioning
confidence: 99%